Diabetes and brain: omics approaches to study diabetic encephalopathy - Lionetti, Nicoletta; Di Lago, Maria Grazia; Brescia, Tania; Bevilacqua, Federica; Gnoni, Antonio (Frontiers in Endocrinology, 2025)
Diabetes mellitus (DM) is a complex metabolic disorder associated with many complications, including diabetic encephalopathy (DE). DE is a severe neurological condition characterized by a progressive decline in cognitive and motor functions, significantly impacting patients’ quality of life. Despite advancements in understanding DM, the intricate pathogenetic mechanisms underlying DE remain incompletely elucidated. This review comprehensively analyzes the application of omics technologies to decipher the molecular basis of DE and identify potential diagnostic biomarkers and therapeutic targets. Several studies on animal models of DE have revealed specific metabolic signatures and changes in gene expression in key memory brain regions, like the hippocampus, highlighting potential therapeutic targets. We explore how these “omics” approaches have provided novel insights into the complex interplay of factors contributing to DE. Recurrent alterations were identified upon evaluation of analysis from human tissues and in vitro models of DE. Findings indicate that this pathological condition is characterized by impaired energy metabolism, oxidative stress, neuroinflammation, neuroendocrine dysfunction and the influence of the gut microbiota. A multi-omics approach, integrating data from various models and limited human studies, enhances translational understanding of DE pathogenesis, with new implications for diagnosis and treatment.